\(=\frac{2+\sqrt{2}-\sqrt{3}+2-\sqrt{6}+\sqrt{8}}{2+\sqrt{2}-\sqrt{3}}=1+\frac{\sqrt{2}\left(2+\sqrt{2}-\sqrt{3}\right)}{2+\sqrt{2}-\sqrt{3}}=1+\sqrt{2}\)
Ta có:
\(\frac{4+\sqrt{2}-\sqrt{3}-\sqrt{6}+\sqrt{8}}{2+\sqrt{2}-\sqrt{3}}\)
\(=\frac{2+\sqrt{2}-\sqrt{3}+2-\sqrt{6}+\sqrt{8}}{2+\sqrt{2}-\sqrt{3}}\)
\(=1+\frac{\sqrt{2}(2+\sqrt{2}-\sqrt{3})}{2+\sqrt{2}-\sqrt{3}}\)
\(=1+\sqrt{2}\)
Vậy \(\frac{4+\sqrt{2}-\sqrt{3}-\sqrt{6}+\sqrt{8}}{2+\sqrt{2}-\sqrt{3}}=1+\sqrt{2}\)
Ta có
\(\frac{4+\sqrt{2}-\sqrt{3}-\sqrt{6}+\sqrt{8}}{2+\sqrt{2}-\sqrt{3}}=\frac{2+\sqrt{2}-\sqrt{3}+2-\sqrt{6}+\sqrt{8}}{2+\sqrt{2}-\sqrt{3}}\)
\(=1+\frac{\sqrt{2}(2+\sqrt{2}-\sqrt{3})}{2+\sqrt{2}-\sqrt{3}}=1+\sqrt{2}\)
\(\text{Vậy }\frac{4+\sqrt{2}-\sqrt{3}-\sqrt{6}+\sqrt{8}}{2+\sqrt{2}-\sqrt{3}}=1+\sqrt{2}\)